2005
DOI: 10.1038/sj.jhh.1001910
|View full text |Cite
|
Sign up to set email alerts
|

Effects of low-dose aspirin on blood pressure and endothelial function of treated hypertensive hypercholesterolaemic subjects

Abstract: The main objective of this study was to assess whether aspirin 100 mg QD can improve blood pressure (BP) control and endothelial function in subjects with arterial hypertension (AH) and hypercholesterolaemia. In total, 21 patients of both sexes (52.1711.5 years) with treated AH and hypercholesterolaemia on antihypertensive and statin therapy were included in the treatment group. In the control group, 20 matched patients of both sexes (51.3712.7 years), but without statin therapy, were recruited. Treatment grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
44
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 33 publications
1
44
0
Order By: Relevance
“…Evidence from explorative clinical trials suggests that treatment with low-dose aspirin increases EDR. In humans, low-dose aspirin administered over a 2-mo period has been found to improve endothelial function (34). In rats with vascular endothelial injury induced by an injection of native LDL, low-dose aspirin is able to reverse the EDR dysfunction (11).…”
mentioning
confidence: 99%
“…Evidence from explorative clinical trials suggests that treatment with low-dose aspirin increases EDR. In humans, low-dose aspirin administered over a 2-mo period has been found to improve endothelial function (34). In rats with vascular endothelial injury induced by an injection of native LDL, low-dose aspirin is able to reverse the EDR dysfunction (11).…”
mentioning
confidence: 99%
“…22,23 On the other hand, Hermida et al reported an inverse association between aspirin intake (100 mg/day) given before bed-time and mean 24 hour BP levels (-6/-4 mm Hg reduction of systolic BP/ diastolic BP) 10 especially in non-dippers. 11 24 Two meta-analyses assessing the association of aspirin and other NSAIDs with BP levels have been published. The first meta-analysis found that among a total of 771 participants, NSAIDs increased mean blood pressure by 5 mm Hg overall (95% CI, 1.2-8.7).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, use of simple drugs such as aspirin may influence endothelial function in hypertension. 3,4 Endothelial cells also facilitate the transport of glucose by GLUT, 5 mainly present in brain barrier, of amino acids (such as L-arginine, a substrate for nitric oxide (NO)). Recent data even suggest a relationship of the endothelium to angiogenesis.…”
mentioning
confidence: 99%